DNA fingerprinting in chicken - Hasima, N.N.; Azli, L.I.; Rahmat, A.A. (Malaysian Society for Molecular Biology and Biotechnology, 1999)
DNA fingerprints of chickens were successfully obtained using a non-radioactive technique. The probe used was the human minisatellite probe, 33.15 and digestions of the genomic DNA were with HaeIII, HinfI and AluI. Average DNA fingerprint band sharing and band frequency between individuals with respect to the different probe-restriction enzyme combinations were used to estimate average band sharing between individuals and average band frequency.